The Kiai's Leadership Model in Shaping Social and Political Life: A Pesantren-Based Perspective in Karangharjo Village - Kholili, Ach; Warits, Abd; Rouf, Muhammad (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2024)
The concept of kiai pemimpinan is a kind of social and political control that is derived from several needs. Kiai dengan sosok elitnya, sebagaimana kelimuan dan keahliannya dalam berbagai bidang menjadi sosok yang dijunjung tinggi. The position of the kiai is very sensitive to changes in the political and social spheres. In addition to serving as a resource for the kiai community, it can also be used as a place for consultation. Desa Karangharjo's children are taught to respect strategic locations, not just as people with a deep understanding of religion but also as good citizens who can uphold social and political stability in the event of conflict. This is the point of contention in this study, which is based on the elit theory proposed by Vilfredo Pareto. This study employs a qualitative approach to phenomenon analysis, which is complemented by a deskriptif critical analysis method. Data collection is done by long-term observation, fieldwork, and documentation. On the other hand, the data analysis used is a deskripsi analysis model that is obtained by primary data collection, data analysis, and kesimpulan reasoning. The following are the main conclusions drawn from this research: a) the specific ways in which the community in Desa Karangharjo is involved in social and political matters; in other words, the community is being transformed into social and political consultants. In addition, kiai serves as an eminent religious figure and a specialist in classical consultation; b) the means of reconciliation between kiai and the Desa Karangharjo community is through interactive communication to understand the current situation. In addition, residents of Desa Karangharjo actively participate in social events and programs that are held in conjunction with the community. This is a type of writing that is often used as a euphemism and can be used to develop social structures, particularly in the village of Karangharjo in Silo, Kabupaten Jember.